Optimal Control of HIV-1 Spread in Combination with Nutritional Status and ARV-Treatment - Yolanda Norasia; Zulaikha Zulaikha; Mohammad Ghani; Denis Sospeter Mukama ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2022)
HIV-1 is a virulent virus, it has the ability to easily spread the virus. This study aims to optimally control the spread of the HIV-1 virus with SIPA (Susceptible-Infection-PreAIDSAIDS) model by using nutritional status and ARV-treatment. Assessment of nutritional status is carried out on people with HIV/AIDS (ODHA). The results showed that the control in the form of nutritional status and ARV-treatment was able to reduce the infected subpopulation. Routine assessment of nutritional status can form balanced nutrition for ODHA. ARV-treatment works by reducing the amount of HIV viral load, so that HIV infection cannot cause disorders of the immune system.